COMPARATIVE MORPHOMETRIC CHARACTERISTICS OF THE RECTUS FEMORIS MUSCLE OF THE HIP ACCORDING TO THE DATA OF THE ULTRASOUND STUDY - Karatieieva, S.Yu.; Slobodian, O.M.; Tsurkan I.М.; Kozlovska, G.O.; Grodetskyy, V.K. (World of Medicine and Biology, 2024)
The study was performed on 48 young men aged 16 to 18. The main group consists of 32 respondents, the control group – of 16 students. All respondents underwent a morphometric study using ultrasound diagnostics of the rectus femoris muscle. As a result of the comparison of the morphometric parameters of the bipinnate (rectus) femoris muscle according to the ultrasound examination, it was established that the volume in the upper third of the m.réctus fémoris is greater in professional football players, compared to student football players, by 31.2 %, by 37.6 %, compared to the control group. Also, in football students the volume of m.réctus fémoris in the upper third is by 9.4 % larger, compared to the control group. In the middle third, it is higher in professional football players by 39.3 % compared to student football players and by 35.4 % compared to the control group. In the lower third, it is higher in professional football players by 28.1 %, compared to student football players, and by 21.1 %, compared to the control group. There is practically no difference in the volume of the m.réctus fémoris in the middle and lower third between football students and the control group.